Sustainable parking management strategy for Tengku Ampuan Afzan Hospital Kuantan - Jamilah, Mohamad (2012)
This study is conducted to study on the efficiency of parking lot management and to assess the provision of additional parking lots based on Cost - Benefit Analysis at Tengku Ampuan Afzan Hospital Kuantan (HTAA). The parking space that have been provided by HTAA is only 964 parking spaces while HTAA has 2414 employees and received approximately 2754 visitors per day and during weekend the number keep increasing. This is 2.5 times overcapacity as compared to the demand by employees alone. Method that been used is License Plate Survey and the survey was conducted on one Wednesday and Sunday. The parking lots are divided into 6 zones and for every one hour, plate numbers of every vehicle was recorded at every 1 hour interval. Questionnaire had also been distributed to 30 respondents to know their opinion about the facilities of provided parking at HTAA.